Comparative study of sublingual versus vaginal misoprostol for induction of labor - Saroha, Indu; Thakur, Sita; Sood, Ajay; Singh, Kamal; Karpa, Monica; Singh, Swarnima (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2020)
Background: Induction of labor done, when the benefits to either mother or fetus outweighs those of continuing pregnancy. Pharmacological methods used for induction includes oxytocin, prostaglandin (E1, E2) and mifepristone. However the ideal dose, route and frequency of administration of misoprostol are still under investigation. Hence we plan to do a comparative study between sublingual and vaginal misoprostol for inducing labor. Methods: A prospective randomized interventional study was conducted on seventy pregnant women who met the inclusion criteria. They were explained about the study on admission and were randomized into two groups: Group I (sublingual) and Group II (vaginal). Bishop score at start of induction, number of pelvic examinations, doses required, mode of delivery, induction to delivery interval, duration of different stages of labor and perinatal outcome of the women were recorded followed by statistical analysis. Results: Patients in both the groups were comparable with respect to demographic data, period of gestation, gravidity and parity. There was no significant difference with regard to number of doses, p/v examinations and number of patients required augmentation. Mean induction to delivery interval, average duration of first, second and third stage was almost comparable. Out of 35 women in each group, 29 women (82.8%) in both groups had normal vaginal delivery, one woman in Group I and three women in Group II had instrumental delivery. Emergency LSCS was done in 5 women (14.28%) in Group I and 3 women (8.57%) in Group II. Conclusions: Sublingual misoprostol seems as effective as vaginal misoprostol for induction of labor at term. Sublingual route represents a valid alternative to vaginal route with the advantage of convenience of administration. In view of limited sample size, we cannot reach definitive conclusions in regard to the preference of sublingual or vaginal route of misoprostol for induction of labor.